Role of texture in hydrogen-induced cracking of steel API 5L X70 under various thermomechanical paths - Masoumi, Mohammad (2017)
Pipeline steels are widely used to transport oil and natural gas in long distance in severe environments. Hydrogen-induced cracking (HIC) is one of the most important failure modes in sour environment. Atomic hydrogen produced during surface pipe corrosion diffuses into the steel and traps at defect sites such as inclusions, precipitations, phase interfaces, martensite islands, and grain boundaries. These hydrogen atoms recombine to form hydrogen molecules, leading to the creation of internal pressure within the metal. This reduces ductility, toughness and mechanical properties, leading to HIC nucleation and propagation. The main objective of this thesis was to find a correlation between a role of texture and grain boundary character distribution with HIC crack nucleation and propagation sites. Finally, proposed thermomechanical treatment produced favorable crystallographic textures and significantly increased HIC resistance which is of great interest to petroleum industry. In this thesis, API 5L X70 steel was subjected to thermomechanical processing with various finish rolling temperatures to produce a similar microstructure with different crystallographic textures. The microstructural and textural evolution was characterised by scanning electron microscopy (SEM), X-ray diffraction (XRD) and electron backscatter diffraction (EBSD). Then, HIC standard test and electrochemical hydrogen-charging experiments were used to induce HIC cracks in pipeline steels. Then EBSD analysis was carried out to show the HIC resistance improvement via appropriate thermomechanical processing. Present work revealed that significant improving of HIC resistance was obtained through engineering of crystallographic texture by isothermal rolling below non-recrystallisation temperature. The high resistance to HIC is highly important to oil and gas transportation. Electron backscatter diffraction (EBSD) measurements were done along the HIC crack in X70 steel after HIC test. The results showed that {001} grains which parallels to normal direction are weak against HIC propagation, and provide a preferred path to crack propagation. Whereas, grains which lied along {110} and {111} planes parallel to rolling plane showed higher resistance against HIC crack nucleation and propagation and improved HIC resistance. In addition, EBSD data revealed that the high amount of recrystallization fraction with no stored energy is one of the main reasons for a higher HIC resistance. Consequently, increasing the fraction of low angle and coincidence site lattice boundaries related to low {hkl} indexing and correspond to the dense planes is targeted in grain boundary engineering to improve HIC resistance. Increasing the number of {111} and {110} grains, with the goal of minimizing the number of {001} grains and HABs, leads to a reduction in crack nucleation and propagation. In overall, the key finding of this work revealed that significant improvement of HIC resistance was obtained through engineering of crystallographic texture by isothermal rolling at approximately 850°C. Although the rolling schedule suggested in the current study differs from the established industrial production, a significant improvement in HIC resistance by controlling of texture only was achieved. This can be a great motivation for development of an alternative thermomechanical treatment with lower finish rolling temperature